A new photocrosslinkable polycaprolactone based ink for three dimensional inkjet printing - He, Yinfeng; Tuck, Christopher; Prina, Elisabetta; Kilsby, Sam; Christie, Steven D.R.; Edmondson, Steve; Hague, Richard J.M.; Rose, Felicity R.A.J.; Wildman, Ricky D. (Wiley, 2017)
A new type of photocrosslinkable polycaprolactone (PCL)-based ink that is suitable for three-dimensional (3D) inkjet printing has been developed. Photocrosslinkable PCL dimethylacrylate was synthesized and mixed with poly(ethylene glycol) diacrylate to prepare an ink with a suitable viscosity for inkjet printing. The ink performance under different printing environments, initiator concentrations, and postprocess was studied. This showed that a nitrogen atmosphere during printing was beneficial for curing and material property optimization, as well as improving the quality of structures produced. A simple structure, building in the z-direction, demonstrated the potential for thismaterial for the production of 3D printed objects. Cells’ testwas carried out to investigate the biocompatibility of the developed ink.